PUBLIC RELATIONS CAMPAIGN IN DISSEMINATING HALAL FOOD AND BEVERAGES TO ELEMENTARY SCHOOL STUDENTS AND THE COMMUNITY - Andri Imam Subekhi; Swastika Oktavia (International Journal Mathla’ul Anwar of Halal Issues, 2021)
This study aims to analyze the public relations campaign in disseminating halal food and beverages to elementary school students and the community carried out by LPPOM MUI Banten. This study discusses issues related to campaign planning, implementation and evaluation. This research is a qualitative research using case study method and constructivism paradigm. Collecting data in this study through observation, interviews and documentation techniques. The results of this study indicate that the public relations campaign in disseminating halal food and beverages to elementary school students and the public by LPPOM MUI Banten is in accordance with the concept of the practical dimensions of the campaign. The planning stage uses analyzing problems, determining goals, determining goals, determining messages, determining time and determining costs. The implementation stage is by selecting the implementer, adjusting the delivery of the message and determining the media used. The evaluation process by looking at the reach of the target and changes in the attitude of the target.